Endovascular Thrombectomy for Carotid Pseudo-Occlusion in the Setting of Acute Ischemic Stroke: A Comparative Systematic Review and Meta-analysis - Toruno, Michelle A.; Meier, Tristan; Elfil, Mohamed; Varshika, Karthi; Cortese, Jonathan; Ghozy, Sherief; Kadirvel, Ramanathan; Kallmes, David F. (American Journal of Neuroradiology, 2024)
BACKGROUND: The effective treatment for patients with acute ischemic stroke (AIS) with cervical internal carotid pseudo-occlusion (cICA-PO) requires comprehensive research on the safety and outcomes of endovascular thrombectomy (EVT). However, there are limited data available, highlighting the need for further research to ensure better treatment strategies and improve the quality of care for these patients.PURPOSE: This study aims to assess the management and outcomes in this population group compared with patients with true carotid occlusion.DATA SOURCES: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, a comprehensive systematic review was conducted by using PubMed, Embase, Web of Science, and Scopus from database inception to November 2023.STUDY SELECTION: The size of the included studies ranged from 16 patients to 146 patients. Through the 4 full-text articles, a total of 259 patients were collected. We compared outcomes between patients with cICA-PO compared with patients with true carotid occlusions undergoing EVT due to AIS. We excluded studies with patients with carotid pseudo-occlusion without stroke, review articles, duplicate studies, overlapped data that included the same patients presented in another included study, case reports, case series with fewer than 5 patients, and meeting abstracts that did not contain the outcomes of interest. We did not pose any limitations regarding sample size or patient characteristics.DATA ANALYSIS: We utilized the R statistical software (V.4.3.1; R package meta) to conduct the analysis of all the data obtained. We calculated the OR for binary variables, and the corresponding 95% CI. To synthesize the data, random-effect models, as well as forest plots were generated to visually represent the synthesis of the data. Additionally, we assessed heterogeneity by using Cochran Q and I2 tests. A P value < .05 for the Q statistic or I2 more than 50% suggests notable heterogeneity. Based on a small number of studies (<10), the assessment of publication bias could not be reliably performed.DATA SYNTHESIS: This meta-analysis encompassed data from 4 studies. Patients with cICA-PO and AIS who underwent EVT (n = 135) exhibited lower rates of functional independence (OR = 0.35; 95% CI, 0.20–0.61; P < .001) compared with patients with true occlusions (n = 103), as well as successful recanalization rates (OR = 0.39; 95% CI, 0.20–0.74; P = .004). In addition, the cICA-PO group experienced higher mortality and symptomatic intracranial hemorrhage (sICH) compared with the group with true carotid occlusions (OR = 2.62; 95% CI, 0.21–7.24; and OR = 2.23; 95% CI, 1.00–4.95; P = .049, respectively).LIMITATIONS: Individual patient data were not available. Studies were a retrospective design and some of the studies had small sample sizes. The included studies in our meta-analysis did not exclude patients with tandem occlusions that might influence the results of the comparison.CONCLUSIONS: Compared with patients with true carotid occlusion, the cICA-PO group with AIS undergoing EVT presented poor outcomes with lower functional independence and successful recanalization, as well as higher sICH and mortality rates.AISacute ischemic strokecICA-POcervical ICA pseudo-occlusionEVTendovascular thrombectomysICHsymptomatic intracranial hemorrhage